Kajian Yuridis Surat Kuasa Membebankan Hak Tanggungan Menurut UU No 2 Tahun 2014 Tentang Jabatan Notaris - Shinta Andriyani (Jatiswara, 2015)
What people deem so far is that the power of attorney to charge mortgage made by a notary is an authentic deed. Yet, they do not realize that only if a notary makes the power of attorney to charge mortgage out of or beyond his/her authority according to law No 02 of 2014 about the function of notaries, the power of attorney will lose its authenticity value. The theme about the power of attorney to charge mortgage made by a notary is strongly interesting to discuss not only to develop our knowledge so that we do not mislead in making the power of attorney to charge mortgage, and at the same time, it will not lose its authenticity value.Besides, this discussion will also figure out the things a notary can make (according his/her authority) in relation with legal action to charge mortgage. Because it is possible for notaries to make a power of attorney to charge mortgage out of or beyond his/her authority will cause the power of attorney to charge mortgage becomes “underhand agreement”, so that its burden of proof is not as strong as authentic deed.